AChR β-Subunit mRNAs Are Stabilized by HuR in a Mouse Model of Congenital Myasthenic Syndrome With Acetylcholinesterase Deficiency - Karmouch, Jennifer; Delers, Perrine; Semprez, Fannie; Soyed, Nouha; Areias, Julie; Bélanger, Guy; Ravel-Chapuis, Aymeric; Dobbertin, Alexandre; Jasmin, Bernard J.; Legay, Claire (Frontiers in Molecular Neuroscience, 2020)
COLQ is a specific collagen that anchors acetylcholinesterase (AChE) in the synaptic cleft of the neuromuscular junction. So far, no mutation has been identified in the ACHE human gene but over 50 different mutations in the COLQ gene are causative for a congenital myasthenic syndrome (CMS) with AChE deficiency. Mice deficient for COLQ mimic most of the functional deficit observed in CMS patients. At the molecular level, a striking consequence of the absence of COLQ is an increase in the levels of acetylcholine receptor (AChR) mRNAs and proteins in vivo and in vitro in murine skeletal muscle cells. Here, we decipher the mechanisms that drive AChR mRNA upregulation in cultured muscle cells deficient for COLQ. We show that the levels of AChR β-subunit mRNAs are post-transcriptionally regulated by an increase in their stability. We demonstrate that this process results from an activation of p38 MAPK and the cytoplasmic translocation of the nuclear RNA-binding protein HuR that interacts with the AU-rich element located within AChR β-subunit transcripts. This HuR/AChR transcript interaction induces AChR β-subunit mRNA stabilization and occurs at a specific stage of myogenic differentiation. In addition, pharmacological drugs that modulate p38 activity cause parallel modifications of HuR protein and AChR β-subunit levels. Thus, our study provides new insights into the signaling pathways that are regulated by ColQ-deficiency and highlights for the first time a role for HuR and p38 in mRNA stability in a model of congenital myasthenic syndrome.